2020
DOI: 10.1097/md.0000000000021276
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of unilateral and bilateral percutaneous balloon kyphoplasty for AOspineA3/A4 osteoporotic thoracolumbar burst fractures

Abstract: To retrospectively evaluate the efficacy and safety of unilateral and bilateral percutaneous balloon kyphoplasty (PKP) in the treatment of osteoporotic thoracolumbar burst fractures. Retrospectively collected clinical data of 138 patients with osteoporotic thoracolumbar burst fractures who underwent unilateral (n = 70) and bilateral (n = 68) PKP in our hospital from March 2015 to December 2018. The general conditions, operation time, radiation exposure time, intraoperative blood loss, bone cement do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 29 publications
(23 reference statements)
0
24
0
Order By: Relevance
“…This method can not only restore vertebral body height and correct vertebral kyphosis deformity, but also reduce pain, the leakage rate of bone cement, and complications, such as nerve injury and pulmonary embolism [ 24 ]. PKP has been reported to be clinically valuable for the treatment of thoracolumbar fracture because of its short operation time, less trauma, low cost, short radiotherapy time, and so on [ 25 ]. This study revealed that there was no significant difference in the peak stress and displacement of the model between PKP and PVP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This method can not only restore vertebral body height and correct vertebral kyphosis deformity, but also reduce pain, the leakage rate of bone cement, and complications, such as nerve injury and pulmonary embolism [ 24 ]. PKP has been reported to be clinically valuable for the treatment of thoracolumbar fracture because of its short operation time, less trauma, low cost, short radiotherapy time, and so on [ 25 ]. This study revealed that there was no significant difference in the peak stress and displacement of the model between PKP and PVP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral and bilateral PKP, as main approaches of this surgery, has been both proved to have an obviously positive effect on OVCF, while unilateral approach seemed to be easy to operate. Recent comparative studies [14,15] found that unilateral PKP are safe and effective for OVCF patients as bilateral PKP, but need less radiation dose, less operation time and fewer cement volume. And several meta-analyses [16][17][18] proposed the similar viewpoints and suggested that unilateral PKP appeared to be superior to bilateral PKP in the treatment of OVCFs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved by many researchers [9][10][11][12] that this surgery can relieve pain symptom, reinstate the vertebral height and restore the spinal alignment immediately, which seal off the gap of the above-mentioned treatment. And several studies [13][14][15] further proved that unilateral PKP has similar effects on pain relief and vertebral height restoration as bilateral PKP, but with shorter surgical time and less blood loss which suggests that this surgery was better for OVCF patients. Nonetheless, it was commonly found in clinical practice that cement was prone to be distributed around injection point and unable to reach the contralateral side of vertebrae, resulting in a symmetrical stress distribution.…”
Section: Introductionmentioning
confidence: 96%
“…Conservative treatment requires long-time bed rest and braking, which increases the risk of accumulation pneumonia, urinary system infection, lower extremity deep venous thrombosis and bedsore. In addition, some patients have fracture nonunion and further collapse of vertebral body, resulting in kyphosis, and develop into chronic pain, even delayed nerve damage, which seriously affects the quality of life of elderly patients [3], and may even endanger their lives due to complications. However, for the majority of AO Spine type A3/A4 elderly osteoporotic thoracolumbar burst fractures are often complicated with basic diseases such as chronic bronchitis, emphysema, coronary atherosclerotic heart disease, or severe trauma and combined injury, and cannot tolerate open surgery under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical operation for burst fractures without neurological de cit remains controversial. For elderly vertebral burst fractures, it is considered as a contraindication because of the concomitant posterior wall rupture and encroachment of the fracture fragment into the spinal canal [3,4].Some scholars [3][4][5][6][7][8] believe that the PVP given to elderly patients with OTLBF has a signi cant effect on the pain level of the patients, and it has a signi cant effect on the correction of kyphosis and the restoration of vertebral height. After considering the patents general condition, we performed the percutaneous vertebroplasty combined with reduction for treating OTLBF,reduce the risk of surgery and xed time to achieve satisfactory results.…”
Section: Introductionmentioning
confidence: 99%